Samuel Van Hoogmoed: Sexual Assult on College Campuses - Van Hoogmoed, Samuel J.
Sexual assault on collage campuses is a topic of great discussion. The current study explores students perceived fears of becoming victims of sexual assault on Fresno State campus grounds and their perceptions concerning current sexual assault prevention policies and methods. Participants were asked to complete a survey to assess the effect that their gender and race had on their fear of being sexually assaulted and their beliefs about Fresno States ability to protect them from sexual assault. Results relieved that gender and race did not have a significant effect on a persons level of fear. Results also concluded that a persons gender did not have a significant effect on a persons perceptions of current campus efforts, however race did in some cases. As for questions about possible improvements that could be made to the campuss security, race and gender had no substantial effect on the responses.